The determinants of Islamic REITs performance in Malaysia: case study of axis REIT / Muhammad Adib Syahir Rusli - Rusli, Muhammad Adib Syahir (Faculty of Business and Management, 2019)
Islamic Real Estate Investment Trusts (I-REITs) have been established to enlarge the scope of Islamic Capital Market in Malaysia. Almost 13 years of establishment of I-REITs since 2006, it is something interesting to study the performance of this Islamic property investment vehicle because it is a potential and different asset class that not fully explored by global investors. This paper investigates the economic factors that can influence the Islamic Real Estate Investment Trust (REIT)’s performance, paying particular attention to the selected Islamic REIT’s company in Malaysia for 7 years quarterly basis from Q1 2011 to Q4 2018 with 32 observations. Study used Net Asset value (NAV) as the proxy for REITs performance while economic growth and inflation rate represent the determinants variable. Applying correlations and multiple regression analysis, the results provide evidence on the association between NAV and economic growth ( GDP ), inflation rate ( CPI ), interest rate ( BLR ) and exchange rate ( EXR ). Results of this study are hoped to help the investors and portfolio managers to deepen their understanding of the dependence factors that might influence the performance of Islamic REITs in Malaysia.